Polycystic ovary syndrome: approach to correction of metabolic disorders - Л. В. Калугіна; Т. Ф. Татарчук (Publishing House TRILIST, 2020)
Objective: to study the reliability of working hypothesis about positive effect of plant adaptogens with hepatoprotective and anti-inflammatory activity in correction of metabolic complications of polycystic ovary syndrome (PCOS) and to study the possibility of including schisandrin into treatment, choice of which is due to its properties to improve tissue sensitivity to insulin, hepatoprotective, hypolipidemic, anti-inflammatory and antioxidant effects. Materials and methods. A comparative prospective study of 60 patients aged 18-38 years with PCOS (phenotype A) was carried out. Criteria for inclusion in the study were: a confirmed diagnosis with increased ovaries and oligo-/anovulation, increased level of ovarian androgens; body mass index (BMI) from 25 to 30.1 kg/m2. All women underwent a general clinical examination evaluating anthropometric parameters and BMI, the presence of clinical manifestations of hyperandrogenism (hirsutism and androgenic dermatopathy) on a Ferriman-Gallwey scale, ultrasound of the genital organs, assessment of progesterone and insulin resistance based on the NOMA index on the 22-24th day of the menstrual cycle. Рatients were divided into 2 equal groups depending on the therapy: women in the main group were prescribed schisandrin 1 tablet (250 mg) three times a day for 12 weeks, patients in the control group received recommendations on diet and physical load. Results. The resulting course of treatment with schisandrin showed restoration of regular menstrual cycles in 40% of patients (versus 16.6% at the beginning of the study) due to a 1.4-fold increase in progesterone level, improvement of skin condition, BMI normalization. A positive effect of treatment on the metabolic status was also noted: a significant decrease in HOMA indices was observed, and transaminases levels were normalized. Conclusions. For a comprehensive examination of patients with PCOS, especially those who are overweight and obese, it is necessary to include a HOMA index assessment, functional liver tests, ultrasound of the hepatobiliary system with elastography. Complex therapy regimen should include schisandrin for prevention of metabolic disorders in women with PCOS and overweight.